Critical thinking how to evaluate information and draw conclusions - Hopkins, John; The Center for Humanities (Mount Kisco, NY : The Center for Humanities)
Demonstrates and encourages effective thinking for making rational decisions. Includes dramatizations of both rational and irrational decisions to help students draw their own conclusions
Title from title screen
Camera and lighting, Bruce Hillyer
Keywords: Interpersonal communication; Communication -- Psychological aspects; Thought and thinking